Three-year outcomes of adults with anxiety and related disorders following cognitive-behavioral therapy in a non-research clinical setting. (April 2015) - Wootton, Bethany M.; Bragdon, Laura B.; Steinman, Shari A.; Tolin, David F.
Highlights: We describe the long-term outcomes of 98 individuals with anxiety and related disorders treated in an outpatient, fee-for-service setting using a case formulation CBT approach. Participants were followed up each year after their discharge, for a period of 3 years. Results indicate that patients maintained their treatment gains, with large effect sizes obtained from pre-treatment to each follow-up time point. The results provide preliminary evidence to suggest that individuals treated with CBT in "real world" settings maintain their treatment gains in the long-term. Abstract: Anxiety and related disorders are highly prevalent and costly to society. Fortunately, a large number of randomized controlled trials have demonstrated the efficacy of cognitive behavioral therapy (CBT) in the treatment of anxiety and related disorders. A smaller number of effectiveness studies have also demonstrated that similar outcomes to randomized controlled trials can be obtained in "real-world" settings. There is minimal research, however, into long-term outcomes in effectiveness research. This study describes the outcomes of 98 individuals with anxiety and related disorders treated in an outpatient, fee-for-service setting using a case formulation CBT approach. Participants were followed up each year after their discharge, for a period of 3 years. The results indicate that patients maintained their treatment gains, with large effect sizes obtained from pre-treatment to each follow-up time point ( d = 1.11–1.60). The results provide preliminary evidence to suggest that individuals treated with CBT in "real-world" settings maintain their treatment gains in the long-term.